Stepping into Virtual Reality - Gutiérrez Alonso, Mario Arturo 1976-; Vexo, Frédéric; Thalmann, Daniel (Springer, 2008)
Virtual reality techniques are increasingly becoming indispensable in many areas. This book looks at how to generate advanced virtual reality worlds. It covers principles, techniques, devices and mathematical foundations, beginning with basic definitions, and then moving on to the latest results from current research and exploring the social implications of these. Very practical in its approach, the book is fully illustrated in colour and contains numerous examples, exercises and case studies. This textbook will allow students and practitioners alike to gain a practical understanding of virtual reality concepts, devices and possible applications.
Keywords: Human-computer interaction; Virtual reality; Virtuelle Realität